A method for purifying molybdenum dichloride dioxide and molybdenum dichloride dioxide
Patent Information
- Application Number
- CN202611086285.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-16
AI Technical Summary
(1)亚稳态MoOx作为钼源,氧缺陷降低了Mo-O键断裂能,可显著降低二氯二氧钼生成温度;氧空位诱导形成选择性氯化路径,抑制高氯化钼副产物生成。
Smart Images

Figure CN122916213A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor precursor preparation technology, specifically to a method for low-temperature solid-phase in-situ preparation of high-purity MoO2Cl2 without chlorine gas or solution. Background Technology
[0002] As semiconductor manufacturing processes shrink, 3D NAND high-stack architectures and GAA devices are being deployed on a large scale, pushing traditional device structures and metal interconnect technologies to their physical and technological limits. In high-stack, high-aspect-ratio structures, traditional CVD tungsten thin films exhibit poor conformal filling, easily generating voids and gap defects. Tungsten fluoride precursors are prone to fluorine residue, corroding high-k dielectrics and silicon oxide dielectric layers, leading to leakage and interface failure. Simultaneously, copper interconnects suffer from electromigration and diffusion defects, resulting in a significant increase in resistivity at nanowire widths and prominent RC delay issues. Molybdenum-based materials, with their low resistivity, high thermal stability, strong anti-electromigration capabilities, and good interface compatibility, have become the mainstream alternative. MoO2Cl2, as a fluorine-free, low-chlorine ALD molybdenum-based precursor, has become a crucial functional material for overcoming technological bottlenecks in advanced memory and logic processes.
[0003] Currently, there are numerous publicly available patents and literature both domestically and internationally disclosing methods for preparing MoO2Cl2, but all of them suffer from some unavoidable technical defects. Patents CN116529206A and TW202132223A use molybdenum oxide as a raw material and react with gaseous chlorine to prepare high-purity MoO2Cl2, achieving a final purity greater than 99.999 wt%. However, high-temperature chlorine is highly corrosive, causing severe equipment corrosion, and the highly toxic chlorine is prone to leakage, posing significant potential risks to personnel safety and environmental pollution. Patent CN119774661A uses a molybdenum-containing solution as a raw material, and after mixing with a calcium source, the resulting molybdenum precipitate is reacted with a chlorinating agent to prepare MoO2Cl2. The XRD pattern in this patent shows characteristic peaks of MoO2Cl2·H2O. However, because the raw material is a molybdenum-containing solution, the resulting molybdenum precipitate contains residual moisture, leading to the direct formation of MoO2Cl2·H2O. This does not effectively demonstrate that the method successfully produced MoO2Cl2. Patent KR10-2714663 uses MoO3 as raw material and thionyl chloride (SOCl2) as chlorinating agent to prepare MoO2Cl2 by reflux reaction in an inert atmosphere with a non-coordinated halogenated solvent. It has advantages such as low reaction temperature and single by-product, but it has defects such as solvent residue, easy hydrolysis of product, large amount of waste liquid and complicated purification process.
[0004] Existing publicly available technologies generally rely on highly toxic chlorine gas / organic solvents / solutions, which suffer from drawbacks such as toxicity, easy hydrolysis, high cost, and poor environmental safety. Furthermore, the similar sublimation temperatures of homologous molybdenum-oxygen-chlorine impurities make them difficult to separate, and they readily hydrolyze to form lattice-bound water. Associated tungsten impurities in the raw materials cannot be routinely removed, and the high specific surface area of the microcrystals easily adsorbs metal dust, thus making it difficult to obtain electronically pure MoO₂Cl₂. Addressing these technological gaps and shortcomings, developing a low-cost, low-pollution, and industrially scalable method for preparing high-purity MoO₂Cl₂ is of great significance. Summary of the Invention
[0005] To address the above problems, this invention provides a method for preparing high-purity MoO2Cl2 through vacuum gradient sublimation purification. The method includes the following steps: In a vacuum environment, molybdenum dichlorodioxygenate is separated from impurities by passing through a three-stage gradient temperature control: a high-temperature sublimation zone, a medium-temperature controllable isothermal transition zone, and a low-temperature deposition crystallization zone.
[0006] Molybdenum dichlorodioxy contains high molybdenum chloride impurities, including 1.2~1.8 wt% molybdenum pentachloride, 0.9~1.5 wt% molybdenum tetrachloride, and 0.5~0.9 wt% molybdenum trichloride.
[0007] The vacuum degree of the vacuum sublimation system is -90 kPa to -99.9 kPa.
[0008] The three-stage gradient temperature vacuum sublimation system consists of: a high-temperature sublimation zone (100-200℃) in the first stage, a controllable isothermal transition zone (80-180℃) in the middle stage, and a low-temperature deposition and collection zone (20-50℃) in the last stage.
[0009] In the preferred scheme, the temperature difference between the high-temperature sublimation zone and the constant-temperature transition zone shall not exceed 50°C, and the temperature difference between the constant-temperature transition zone and the low-temperature deposition and collection zone shall not exceed 100°C.
[0010] In the preferred embodiment, the three-stage gradient temperature vacuum sublimation system consists of: a high-temperature sublimation zone at the front (150-200°C), a controllable constant-temperature transition zone at the middle (120-160°C), and a low-temperature deposition and collection zone at the rear (40-50°C).
[0011] Multi-temperature zone vacuum sublimation apparatus is used for the separation and purification of impurities in crude MoO2Cl2. The composite reaction powder is initially in the high-temperature sublimation zone, and the synthesis and sublimation zones are located at the same location. The synthesis is not in a vacuum state. After the synthesis is completed, the system is switched to a vacuum for sublimation purification. The synthesized crude MoO2Cl2 is also in the sublimation zone. Vacuum sublimation is usually divided into three zones: high-temperature sublimation zone, isothermal transition zone, and low-temperature collection zone. Finally, high-purity MoO2Cl2 is deposited in the collection zone.
[0012] After purification, the process also includes inert protection, cooling, and encapsulation. Specifically, the product is cooled naturally in a vacuum environment, and then argon gas is introduced to break the vacuum and return the vacuum system to normal pressure or slightly positive pressure. The product is then collected and vacuum-sealed for preservation under the protection of an inert atmosphere.
[0013] The preparation steps of the aforementioned molybdenum dichlorodioxydioxide are as follows: (1) Preparation of metastable nano molybdenum oxide powder: molybdenum trioxide was heated and reduced in a reducing atmosphere to obtain metastable MoOx; (2) Anhydrous dry mixing: Metastable MoOx, solid chlorine source and inert composite heat carrier are dry ball milled and mixed in an inert gas environment to obtain uniform composite powder; (3) Low-temperature in-situ solid-phase synthesis: The composite powder is heated and reacted under an inert atmosphere to obtain molybdenum dichlorodioxy.
[0014] The purity of molybdenum trioxide mentioned in step (1) is >99.99%; the reducing atmosphere is a 5%~10% H2 / Ar mixed gas, the flow rate is 150~300mL / min, the heating temperature is 250~400℃, and the reaction time is 2~5h; The metastable MoOx has a value in the range of 2 to 3. The presence of oxygen vacancies in the metastable state reduces the Mo-O bond breaking energy, which can significantly lower the formation temperature of molybdenum dichlorodioxygenate. At the same time, oxygen vacancies induce the formation of a selective chlorination pathway.
[0015] In some preferred embodiments, the anhydrous dry batching in step (2) can be carried out in a glove box.
[0016] The solid chlorine source in step (2) is anhydrous metal chloride MCl. n Complex systems with alkali metal salts, or anhydrous non-metallic organochlorine sources; Anhydrous metal chloride MCl n M is selected from any one or more combinations of Al, Zn, Fe, Cu, Ni, Cr, Pb, Mn, and Co, and n is 1 to 4; n refers to the number of moles of M with conventional stability in its valence state (n is numerically equal to the current positive valence of M in the chloride).
[0017] Alkali metal salts are selected from any one or a combination of NaCl, KCl, and LiCl; The anhydrous non-metallic organochlorine source is selected from hexachlorobenzene or cyanuric chloride.
[0018] The present invention uses a solid chlorine source mainly to replace the toxic gas chlorine commonly used in previous patents. Solid materials are safe and environmentally friendly.
[0019] In some preferred embodiments, the anhydrous metal chloride MCln and alkali metal salt complex system is selected from MCln-NaCl, MCln-KCl binary complex system or MCln-MCln-NaCl ternary complex system.
[0020] Anhydrous metal chlorides MCln can form low-temperature eutectic salts with alkali metal salts NaCl or KCl, lowering the activation temperature and allowing the anhydrous metal chlorides to release chlorine components at lower temperatures. The preferred mass ratio of the binary composite systems MCln-NaCl and MCln-KCl is 2-5:1, and more preferably 2:1; the preferred mass ratio of the ternary composite system MCln-MCln-NaCl is 1:2-1:2-1, and more preferably 1:1:1.
[0021] The inert heat carrier mentioned in step (2) is selected from any one or a combination of boron nitride, quartz powder, silicon carbide, silicon nitride, and fumed silica.
[0022] In step (2), the mass ratio of MoOx, solid chlorine source and inert heat carrier is 10:(3~4):(2~2.5), the dry ball milling time is 30~90min, and the particle size of the uniform composite powder is 300~500 mesh.
[0023] Regarding the aforementioned mass ratio, using 10 parts of metastable MoOx as the reaction baseline, 3-4 parts of anhydrous solid chlorine source can provide a slightly excessive amount of active chlorine component, matching the large number of oxygen defect sites on the surface of the molybdenum source, ensuring the efficient conversion of molybdenum component to molybdenum dichlorodioxygenate, with a single-pass molybdenum conversion rate of not less than 92%. When the amount of chlorine source added is less than 3 parts, the supply of active chlorine is insufficient, the internal reaction of the material is incomplete, and the conversion rate decreases significantly. When the amount of chlorine source added exceeds 4 parts, it is easy to trigger a deep chlorination side reaction, producing a low-valence molybdenum chloride impurity phase. At the same time, the excessive sublimation of aluminum and zinc gas phases in the solid chlorine source is difficult to completely retain, and the metal impurities in the product exceed the standard.
[0024] The amount of inert heat carrier added is controlled at 2~2.5 parts, which can uniformly disperse the reaction powder and build loose and interconnected pore channels. This not only homogenizes the temperature of the reaction bed and eliminates local hot spots, but also significantly improves the diffusion mass transfer rate of gaseous active chlorine, shortening the isothermal synthesis time by more than 25%. Insufficient carrier addition will lead to dense powder accumulation and hindered mass transfer, while excessive carrier will dilute the molybdenum source loading, reduce the single furnace capacity, and cause product gas phase adsorption loss.
[0025] The inert atmosphere mentioned in step (3) is selected from high-purity argon and nitrogen, both with a purity greater than 99.999%; Before heating, the reaction environment is replaced with argon and / or nitrogen at a flow rate of 200-300 mL / min for 10-30 min. The furnace is kept under a slight positive pressure throughout the process, with a gauge pressure of 200 Pa-1000 Pa.
[0026] In some specific embodiments, the gas phase replacement is achieved by replacing the gas phase with high-purity argon or nitrogen to reduce the amount of air, water vapor, and oxygen impurities in the equipment to less than 1 ppm.
[0027] A slight positive pressure in the system can effectively prevent air and impurities from entering the synthesis system, which can greatly improve the synthesis conversion rate and avoid impurities from causing side reactions.
[0028] In the low-temperature in-situ solid-phase synthesis reaction described in step (3), the heating rate is (5~10)℃ / min, the isothermal reaction temperature is 220~300℃, the reaction time is 3~5h, and the reaction system is completely sealed.
[0029] Step (3) also includes a post-reaction processing step. Specifically, after the synthesis is completed, the mixture is allowed to cool naturally in a sealed environment, and then argon gas is introduced to break the vacuum and return the vacuum system to normal pressure or slightly positive pressure. The product is collected under an inert atmosphere and vacuum-sealed for storage. The entire process of product collection and packaging is completed in an argon / nitrogen glove box with a water and oxygen content of <1ppm, and the product is stored in vacuum aluminum-plastic packaging or ampoules sealed by melting.
[0030] A molybdenum dichlorodioxygenate obtained by the purification method described above, wherein the purity of the molybdenum dichlorodioxygenate is greater than 5N; The total amount of the metallic impurities is less than 10 ppm, preferably less than 5 ppm, preferably less than 3 ppm, preferably less than 2 ppm, and preferably less than 1 ppm.
[0031] The single-metal impurity content in molybdenum dichlorodioxy is less than 0.5 ppm, preferably less than 0.3 ppm, more preferably less than 0.2 ppm, more preferably less than 0.1 ppm, and more preferably less than 0.05 ppm; The metallic impurities include one or more of Ag, Al, As, Au, Ba, Be, Bi, B, Ca, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, K, Li, Mg, Mn, Na, Nb, Ni, Pb, Pd, Pt, Sb, Se, Sr, Sn, Ta, Ti, Tl, Th, U, V, W, Zn, and Zr.
[0032] The application of molybdenum dichlorodioxy in semiconductor ALD / CVD fluorine-free molybdenum thin film precursors, 3D NAND high-stack architectures, or GAA devices.
[0033] The method provided by this invention effectively reduces the generation temperature of MoO2Cl2 and avoids the defects of strong corrosion and toxicity caused by the introduction of high-temperature chlorine gas. It has the advantages of low energy consumption, low cost, safety and environmental protection.
[0034] Compared with the prior art, the present invention has the following advantages: (1) Metastable MoOx serves as a molybdenum source. Oxygen defects reduce the Mo-O bond breaking energy, which can significantly reduce the molybdenum dichlorodioxygenation generation temperature. Oxygen vacancies induce the formation of a selective chlorination pathway, which inhibits the generation of high-chlorinated molybdenum byproducts.
[0035] (2) Anhydrous composite solid chlorine source is used as chlorinating agent. No chlorine gas is introduced, the process is safe, the system is completely free of crystal water, and the hydrolysis of MoO2Cl2 is avoided from the source.
[0036] (3) Inert heat carrier can disperse powder to prevent raw material agglomeration and sintering and local overheating, inhibit the generation of by-products, and form loose pore channels to facilitate the diffusion of gaseous active chlorine components and improve the raw material conversion rate.
[0037] (4) The synthesis reaction-vacuum sublimation device is integrated, which avoids secondary pollution when the material is transferred to the purification process after the reaction is completed. Attached Figure Description
[0038] Figure 1 Schematic diagram of an integrated solid-phase in-situ synthesis-vacuum sublimation purification device.
[0039] Figure 2 A physical image of the preparation and purification process of MoO2Cl2 in a certain example.
[0040] Figure 3 X-ray diffraction pattern of the purified MoO2Cl2 prepared in Example 1. Detailed Implementation
[0041] To better explain the implementation process of this invention, an integrated vacuum sublimation purification device of this invention is provided, such as... Figure 1 Show. Figure 1 101 is the inlet pipe of the device, used for introducing an inert atmosphere into the displacement tubular reactor.
[0042] 102 is a composite powder of MoOx, chlorinating agent and inert heat-conducting carrier, and 103 is a high-purity quartz boat; that is, the composite powder of MoOx, chlorinating agent and inert heat-conducting carrier reacts in a high-purity quartz boat in a tube-type reactor.
[0043] 104 is the lower resistance heating element, and 105 is the upper resistance heating element; these are used to control the temperature inside the tubular reactor.
[0044] 106 is a high-purity quartz inner tube, and 107 is a segmented high-purity quartz outer tube; 108 is a vacuum extraction port, used to achieve a slightly positive pressure vacuum state inside the tubular reactor.
[0045] The inner tube appears to have three sections, made of quartz glass. The outer tube is divided into heating temperature sections. The inner tube is divided into several sections simply to facilitate material feeding and discharging. The material is added into the outer tube through the inner tube containing the quartz boat under the protection of inert gas.
[0046] Currently, it seems Figure 2 From left to right, it can be seen that the material in the first sublimation zone is the purified heavy component impurity, the material in the second transition zone is a smaller amount of heavy component impurity and a small amount of MoO2Cl2 (purity lower than that in the collection zone), and the material in the third collection zone is high-purity MoO2Cl2. In addition, the lighter components are directly pumped to the light component retention zone before the pump and cannot be observed in the quartz tube.
[0047] In a specific embodiment, the content of metal impurity ions in the sublimated and purified product was detected by ICP-MS analysis.
[0048] Comparative Example 1 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx and 6g anhydrous solid chlorine source (AlCl3-NaCl, mass ratio 2:1) are accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder; S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove impurities, including air. The composite powder is then moved into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 230℃, and the closed constant temperature reaction time is 3h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to the vacuum environment. The system vacuum degree is -99Kpa. The first high-temperature sublimation zone is 150℃, the middle controllable isothermal transition zone is 140℃, and the last low-temperature condensation and collection zone is 50℃ to complete the vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0049] In this example, after the above steps, 14.34g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield of only 57.54%.
[0050] Comparative Example 2 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a single temperature zone in a tube furnace, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200mL / min. The reduction reaction is carried out for 5h to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (AlCl3-NaCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove impurities, including air. The composite powder is then moved into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 230℃, and the closed constant temperature reaction time is 3h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to vacuum environment. The system vacuum degree is -99Kpa. The first high temperature sublimation zone is 210℃, the middle controllable isothermal transition zone is 130℃, and the last low temperature condensation collection zone is 10℃ to complete vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0051] In this example, after the above steps, 14.31g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield of only 57.42%.
[0052] Example 1 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (AlCl3-NaCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove impurities, including air. The composite powder is then moved into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 230℃, and the closed constant temperature reaction time is 3h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to the vacuum environment. The system vacuum degree is -99Kpa. The first high-temperature sublimation zone is 150℃, the middle controllable isothermal transition zone is 140℃, and the last low-temperature condensation and collection zone is 50℃ to complete the vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0053] In this example, after the above steps, 22.15g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 88.88%.
[0054] Example 2 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (ZnCl2-NaCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and uniformly mixed and ground by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then moved into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 250℃, and the closed constant temperature reaction time is 4h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to vacuum environment. The system vacuum degree is -99Kpa. The first high temperature sublimation zone is 160℃, the middle controllable isothermal transition zone is 130℃, and the last low temperature condensation collection zone is 50℃ to complete vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0055] In this example, after the above steps, 19.62g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 78.73%.
[0056] Example 3 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (FeCl3-NaCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then transferred into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 280℃, and the closed constant temperature reaction time is 4h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to vacuum environment. The system vacuum degree is -99Kpa, the first high temperature sublimation zone is 110℃, the middle controllable constant temperature transition zone is 80℃, and the last low temperature condensation collection zone is 30℃ to complete vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0057] In this example, after the above steps, 20.86g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 83.27%.
[0058] Example 4 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a single temperature zone in a tube furnace, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (CuCl2-NaCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then transferred into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 250℃, and the closed constant temperature reaction time is 3h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to the vacuum environment. The system vacuum degree is -99Kpa. The first high-temperature sublimation zone is 120℃, the middle controllable isothermal transition zone is 100℃, and the last low-temperature condensation collection zone is 45℃ to complete the vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0059] In this example, after the above steps, 20.39g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 81.82%.
[0060] Example 5 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a single temperature zone in a tube furnace, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (AlCl3-KCl, mass ratio 2:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then transferred into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 230℃, and the closed constant temperature reaction time is 3h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to the vacuum environment. The system vacuum degree is -99Kpa. The first high-temperature sublimation zone is 180℃, the middle controllable isothermal transition zone is 150℃, and the last low-temperature condensation collection zone is 50℃ to complete the vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0061] In this example, after the above steps, 21.83g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 87.60%.
[0062] Example 6 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: 20g MoOx, 6g anhydrous solid chlorine source (AlCl3-ZnCl2-NaCl, mass ratio 1:1:1) and 4g hexagonal boron nitride were accurately weighed in the glove box and mixed and ground evenly by dry ball milling for 30 minutes in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then transferred into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 240℃, and the closed constant temperature reaction time is 5h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to vacuum environment. The system vacuum degree is -99Kpa. The first high temperature sublimation zone is 170℃, the middle controllable isothermal transition zone is 150℃, and the last low temperature condensation collection zone is 45℃ to complete vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0063] In this example, after the above steps, 19.65g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 78.85%.
[0064] Example 7 S1: Add 50g of MoO3 raw material with a purity greater than 99.99% to a quartz boat in a quartz tube, heat it to 350℃ in a tube furnace in a single temperature zone, and then introduce 5% H2 / Ar mixed gas at a gas flow rate of 200 mL / min. The reduction reaction is carried out for 5 hours to obtain metastable MoOx intermediate. S2: Accurately weigh 20g MoOx, 6g anhydrous hexachlorobenzene, and 4g (fused silica powder - high-purity silicon carbide powder, mass ratio 1:1) in a glove box and mix and grind them evenly for 30 minutes using dry ball milling in an anhydrous and oxygen-free glove box to finally obtain composite powder. S3: The multi-temperature zone closed reaction device is pre-purified with high-purity argon gas through multiple replacements to remove air. The composite powder is then moved into the reaction device under inert atmosphere protection. The heating rate is set to 10℃ / min, the constant temperature reaction temperature is 230℃, and the closed constant temperature reaction time is 4h. There is no tail gas emission throughout the process. S4: After the synthesis reaction is completed, switch to the vacuum environment. The system vacuum degree is -99Kpa. The first high-temperature sublimation zone is 130℃, the middle controllable isothermal transition zone is 100℃, and the last low-temperature condensation collection zone is 40℃ to complete the vacuum gradient sublimation purification. S5: Weigh, package and store the product collected after vacuum sublimation purification in a glove box; and test and analyze the content of metal impurity ions in the collected product.
[0065] In this example, after the above steps, 21.41g of high-purity MoO2Cl2 product was finally obtained, with a theoretical yield of 24.92~27.86g and a yield as high as 85.91%.
[0066] Table 1 below summarizes the relevant process parameters, yields, and purities for Examples 1-7.
[0067] Table 2 below shows the metal ion impurity content of MoO2Cl2 products from Comparative Example 2 and the Example, as determined by ICP-MS. Comparative Example 2
[0068] Example 1
[0069] Example 3
[0070] Example 5
[0071] Comparative Example 2 had a total impurity content higher than 30 ppm, and the purity of the prepared MoO2Cl2 was lower than 99.999 wt%, failing to reach the 5N level. Examples 1, 3, and 5 all had total impurities lower than 3 ppm (<0.01 is below the detection limit and is not counted), and the purity of the prepared MoO2Cl2 was greater than 99.999 wt%, reaching the 5N level.
[0072] The specific embodiment of the present invention adopts the method of low-temperature solid-phase in-situ preparation of high-purity MoO2Cl2 without chlorine gas or solution, and purification by vacuum gradient sublimation. The purity of the products in Examples 1-7 can all reach the 5N level. Figure 3 The X-ray diffraction pattern of MoO2Cl2, the purified product of Example 1, shows that since this substance readily absorbs water upon contact with air, the XRD pattern detected characteristic peaks of both MoO2Cl2 and MoO2Cl2·H2O. There were no other impurity peaks, which indirectly indicates that the MoO2Cl2 prepared by this method has high purity.
[0073] Various modifications and improvements made by those skilled in the art without departing from the technical concept of this invention are all within the scope of protection defined by the claims of this invention.
Claims
1. A method for purifying molybdenum dichlorodioxy, characterized in that, Includes the following steps: In a vacuum environment, molybdenum dichlorodioxygenate is separated from impurities by passing through a three-stage gradient temperature control: a high-temperature sublimation zone, a medium-temperature controllable isothermal transition zone, and a low-temperature deposition crystallization zone.
2. The purification method for molybdenum dichlorodioxy according to claim 1, characterized in that, Molybdenum dichlorodioxydioxide contains high molybdenum chloride impurities, including 1.2~1.8 wt% molybdenum pentachloride, 0.9~1.5 wt% molybdenum tetrachloride, and 0.5~0.9 wt% molybdenum trichloride.
3. The purification method for molybdenum dichlorodioxy according to claim 1, characterized in that, The vacuum degree of the vacuum sublimation system is -90 kPa to -99.9 kPa.
4. The purification method for molybdenum dichlorodioxy according to claim 1, characterized in that, The three-stage gradient temperature vacuum sublimation system consists of: a high-temperature sublimation zone (100-200℃) in the first stage, a controllable isothermal transition zone (80-180℃) in the middle stage, and a low-temperature deposition and collection zone (20-50℃) in the last stage.
5. The purification method for molybdenum dichlorodioxy according to claim 1, characterized in that, The three-stage gradient temperature vacuum sublimation system consists of: a high-temperature sublimation zone at the front (150-200℃), a controllable isothermal transition zone at the middle (120-160℃), and a low-temperature deposition and collection zone at the rear (40-50℃).
6. The purification method for molybdenum dichlorodioxy according to claim 1, characterized in that, After purification, the process also includes inert protection, cooling, and encapsulation. Specifically, the product is cooled naturally in a vacuum environment, and then argon gas is introduced to break the vacuum and return the vacuum system to normal pressure or slightly positive pressure. The product is then collected and vacuum-sealed for preservation under the protection of an inert atmosphere.
7. The purification method for molybdenum dichlorodioxy according to any one of claims 1-6, characterized in that, The preparation steps of the aforementioned molybdenum dichlorodioxydioxide are as follows: (1) Preparation of metastable nano molybdenum oxide powder: molybdenum trioxide was heated and reduced in a reducing atmosphere to obtain metastable MoOx; (2) Anhydrous dry mixing: Metastable MoOx, solid chlorine source and inert composite heat carrier are dry ball milled and mixed in an inert gas environment to obtain uniform composite powder; (3) Low-temperature in-situ solid-phase synthesis: The composite powder is heated and reacted under an inert atmosphere to obtain molybdenum dichlorodioxy.
8. A molybdenum dichlorodioxygenate, characterized in that, The molybdenum dichlorodioxydioxide prepared by the method according to any one of claims 1-7 has a purity greater than 5N; The total amount of the metallic impurities is less than 10 ppm, preferably less than 5 ppm, preferably less than 3 ppm, preferably less than 2 ppm, and preferably less than 1 ppm.
9. The molybdenum dichlorodioxygenate according to claim 8, characterized in that, The single-metal impurity content in molybdenum dichlorodioxy is less than 0.5 ppm, preferably less than 0.3 ppm, more preferably less than 0.2 ppm, more preferably less than 0.1 ppm, and more preferably less than 0.05 ppm; The metallic impurities include one or more of Ag, Al, As, Au, Ba, Be, Bi, B, Ca, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, K, Li, Mg, Mn, Na, Nb, Ni, Pb, Pd, Pt, Sb, Se, Sr, Sn, Ta, Ti, Tl, Th, U, V, W, Zn, and Zr.
10. The application of molybdenum dichlorodioxy as described in claim 8 or 9 in semiconductor ALD / CVD fluorine-free molybdenum thin film precursors, 3D NAND high-stack architectures, or GAA devices.
Citation Information
Patent Citations
Molybdenum dioxide dichloride preparation method based on molybdenum-containing solution
CN119774661A
Method for production of molybdenum dioxide dichloride
KR102714663B1
High-purity molybdenum oxychloride and manufacturing method therefor
TW202132223A